Attractors for Nonlinear Autonomous Dynamical Systems - Qin, Yuming; Su, Keqin (Current Natural Sciences, 2022)
This book introduces complete and systematic theories of infinite-dimensional dynamical systems and their applications in partial differential equations, especially in the models of fluid mechanics. It is based on the first author's lecture "Infinite dimensional dynamical systems on nonlinear autonomous systems" given to graduate students in Donghua University since 2004. This book presents recent results that have been carried out by the authors on autonomous nonlinear evolutionar yequations arising from physics, fluid mechanics and material science such as the Navier-Stokes equations, Navier-Stokes-Voight systems, the nonlinear thermoviscoelastic system, etc